Physico-chemical properties of edible films derived from native and phosphated cush-cush yam and cassava starches - Gutiérrez, Tomy J. (2015)
Edible, biodegradable films based on native and phosphated cush-cush yam and cassava starches plasticized with glycerol were developed by casting. The starches were chemically modified by cross-linking with sodium trimetaphosphate (STMP). The physicochemical properties of each of the different starch films were then evaluated and compared in order to determine their potential applications in the food industry. The amylose molecules in the cassava starch strongly interacted with glycerol resulting in an increase in the number of hydrogen bonds. This led to a slight shift upwards in the temperature required for the onset of the degradation of the cassava starch-based films, and even higher temperatures for degrading the films based on the modified starches. Films made from phosphated starches were more hydrophilic, producing an increase in solubility and crystallinity. Finally, the characteristics of the cassava films developed suggest that they would make good packaging materials, while films derived from cush-cush yam are more suitable as food coatings.